2021
DOI: 10.1186/s12917-021-02911-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional differentiation related to decomposing complex carbohydrates of intestinal microbes between two wild zokor species based on 16SrRNA sequences

Abstract: Background The intestinal microbes in mammals play a key role in host metabolism and adaptation. As a subterranean rodent, zokor digs tunnels for foraging and mating. These digging activities of zokors increase the energy expenditure relative to their aboveground counterparts. However, relatively little is known regarding intestinal microbes of zokor and how they make full use of limited food resources underground for high energy requirements. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Studies have shown that zokor is a pure herbivorous animal, with a well-developed cecum for decomposing cellulose in plants [50]. Meanwhile, we classified the fungi groups obtained, and found that they were mainly pathogenic fungi of plants, endophytic fungi, fungi in soil, and fungi intrinsic to the stomach of zokor, but not large edible fungi.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies have shown that zokor is a pure herbivorous animal, with a well-developed cecum for decomposing cellulose in plants [50]. Meanwhile, we classified the fungi groups obtained, and found that they were mainly pathogenic fungi of plants, endophytic fungi, fungi in soil, and fungi intrinsic to the stomach of zokor, but not large edible fungi.…”
Section: Resultsmentioning
confidence: 93%
“…The rat mainly feeds on taproots(54.60%) and rhizomes(26.41%),( Table 4 .) which are rich in water and energy, which can meet the high energy consumption caused by zokor’s digging habit [50].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 99.81% of the effective ASV sequences were annotated to Eukaryota, among which Fungi accounted for 69.55%, Viridiplantae was 29.52%, Metazoa was 0.82%, and unclassified was only 0.11%. Studies have shown that zokors are purely herbivorous animals possessing a well-developed cecum for decomposing cellulose in plants [ 26 ],this study focused on Viridiplantae.…”
Section: Resultsmentioning
confidence: 99%
“…Plants in the zokor’s diet could also be classified according to the plant parts that zokors feed on. Zokors mainly feed on taproots (54.60%) and rhizomes (26.41%)( Table 4 ), which are rich in water and energy and thus can meet the high energy consumption requirements caused by the zokor’s digging habits [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gut microbiota are mainly influenced by host genetics and environmental factors [ 40 ], and food has frequently been reported to be the main factor [ 41 , 42 ]. When comparing the species in our study, the bacterial community compositions of the whole GIT, as well as each segment, were significantly different.…”
Section: Discussionmentioning
confidence: 99%